STRONG RESONANCES AT HIGH EXCITATION ENERGY IN 17O+ALPHA RESONANCE SCATTERING - Nauruzbayev, D. K.; Nurmukhanbetova, A. K.; Goldberg, V. Z.; Cognata, M. La; Pietro, A. Di; Figuera, P.; Cherubini, S.; Gulino, M.; Lamia, L.; Pizzone, R. G.; Spartà, R.; Tumino, A.; et al. (arxiv, 2019)
The Thick Target Inverse Kinematic (TTIK) approach was used to measure excitation functions for the elastic 17O (α, α) scattering at the initial 17O beam energy of 54.4 MeV. We observed strong peaks corresponding to highly excited α-cluster states in the 21Ne excitation energy region of 8-16 MeV, which have never been investigated before. Additional tests were done at a 17O beam energy of 56.4 MeV to estimate a possible contribution of resonance inelastic scattering
Keywords: Type of access: Open Access; 17O+ALPHA RESONANCE SCATTERING